An investigation into 88 KV surge arrester failures in the Eskom east grid traction network - Mzulwini, Mduduzi Comfort (Department of Electrical Engineering, 2023)
The Eskom East Grid Traction Network (EGTN) supplying traction loads and distribution networks has experienced at least one surge arrester failure over the past ten years. These failures results in poor network reliability and customer dissatisfactions which are often overlooked. This is because reliability indices used in the reliability evaluation of transmission and distribution networks are different. It is suspected that fast transient faults in this network initiate system faults leading to surge arrester design parameter exceedances and poor network insulation coordination. Preliminary investigations in network suggest that transient studies were not done during network planning and design stages. This may have resulted in the lack of surge arrester parameter evaluations under transient conditions leading to improper surge arresters being selected and installed in this network resulting in surge arrester failures that are now evident. These failures may also have been exacerbated by the dynamic nature of traction loads as they are highly unbalanced, have poor power factors and emit high voltage distortions. Poor in-service conditions such as defects, insulation partial discharges and overheating, bolted faults in the network and quality of supply emissions can also contribute to surge arrester failures. To address problems arising with different reliability indices in these networks the reliability of the EGTN is evaluated. In this work the reliability evaluation of the EGTN is done by computing common distribution reliability indices using analytic and simulation methods. This is done by applying the analytic method in the EGTN by assessing network failure modes and effects analysis (FMEA) when the surge arrester fails in this network. The simulation method is applied by applying and modifying the MATLAB code proposed by Shavuka et al. [1]. These reliability indices are then compared with transmission reliability indices over the same period. This attempts to standardize reliability evaluations in these networks. To assess the impact of transient faults in the surge arrester parameter evaluation the EGTN is modelled and simulated by initiating transient faults sequentially in the network at different nodes and under different loading conditions. This is done by using Power System Blockset (PSB), Power System Analysis Toolbox (PSAT) and Alternate Transient Program (ATP) simulation tools and computing important surge arrester parameters i.e. continuous operating voltage, rated voltage, discharge current and energy absorption capability (EAC). These parameters are assessed by in the EGTN by evaluating computed surge arrester parameters against parameters provided by manufacturers, the Eskom 88 kV surge arrester specification and those parameters recommended in IEC 60099-4. To assess the impact and contribution of in-service conditions, faults and quality of supply emissions in surge arrester failures these contributing factors are investigated by assessing infra-red scans, fault analysis reports, results of the sampled faulted surge arrester in this network and quality of supply parameters around the time of failures. This study found that Eskom transmission and distribution network reliability indices can be standardized as distribution reliability indices i.e. SAIDI, SAIFI, CAIDI, ASAI and ASUI indices are similar to Eskom transmission indices i.e. SM, NOI, circuit availability index and circuit unavailability index respectively. Transient simulations in this study showed that certain surge arresters in the EGTN had their rated surge arrester parameters exceeded under certain transient conditions and loading conditions. These surge arresters failed as their discharge currents and EACs were exceeded under heavy and light network loading conditions. This study concluded that surge arresters whose discharge currents and EACs exceeded were improperly evaluated and selected prior to their installations in the EGTN. This study found the EAC to be the most import parameter in surge arrester performance evaluations. The Eskom 88 kV surge arrester specification was found to be inadequate, inaccurate and ambiguous as a number of inconsistencies in the usage of IEEE and IEC classified systems terminology were found. It was concluded that these inconsistencies may have led to confusions for manufacturers during surge arrester designs and selections in the EGTN. The evaluation of fault reports showed that two surge arrester failures in this network were caused by hardware failures such as conductor failure and poor network operating as the line was continuously closed onto a fault. There was no evidence that poor in-service and quality of supply emissions contributed to surge arrester failures in this network. PSB, PSAT and ATP simulation tools were found adequate in modelling and simulating the EGTN. However the PSB tool was found to be slow as the network expanded and the PSAT required user defined surge arrester models requiring detailed manufacture data sheets which are not readily available. ATP was found to be superior in terms of speed and accuracy in comparison to the PSB and PSAT tools. The MATLAB code proposed by Shavuka et al. [1] was found to be suitable and accurate in assessing transmission networks as EGTN's reliability indices computed from this code were comparable to benchmarked Eskom distribution reliability indices. The work carried out in this research will assist in improving surge arrester performance evaluations, the current surge arrester specification and surge arrester selections. Simulation tools utilized in this work show great potential in achieving this. Reliability studies conducted in this work will assist in standardizing reliability indices between Eskom's transmission and distribution divisions. In-service condition assessment carried out in this work will improve surge arrester condition monitoring and preventive maintenance practices.